2015
DOI: 10.1038/ncomms7734
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-sensing receptors GPR43 and GPR109A facilitate dietary fibre-induced gut homeostasis through regulation of the inflammasome

Abstract: Diet and the gut microbiota may underpin numerous human diseases. A major metabolic product of commensal bacteria are short-chain fatty acids (SCFAs) that derive from fermentation of dietary fibre. Here we show that diets deficient or low in fibre exacerbate colitis development, while very high intake of dietary fibre or the SCFA acetate protects against colitis. SCFAs binding to the 'metabolite-sensing' receptors GPR43 and GPR109A in non-haematopoietic cells mediate these protective effects. The inflammasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
935
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,101 publications
(973 citation statements)
references
References 48 publications
27
935
1
10
Order By: Relevance
“…13,39,40 Activation of GPR43 by acetate leads to colonic epithelial hyperpolarization, which was accompanied by a reduction in apoptosis. 11 We found, however, that Gpr43 and other metabolite-sensing G proteincoupled receptors previously associated with SCFAs such as the olfactory receptor (Olfr78) 41 were not expressed in the kidney or heart (data not shown). Gpr43 mRNA was also downregulated in the gut with mineralocorticoid excess independently of the treatment group (data not shown).…”
Section: Cardiac Transcriptomementioning
confidence: 64%
See 2 more Smart Citations
“…13,39,40 Activation of GPR43 by acetate leads to colonic epithelial hyperpolarization, which was accompanied by a reduction in apoptosis. 11 We found, however, that Gpr43 and other metabolite-sensing G proteincoupled receptors previously associated with SCFAs such as the olfactory receptor (Olfr78) 41 were not expressed in the kidney or heart (data not shown). Gpr43 mRNA was also downregulated in the gut with mineralocorticoid excess independently of the treatment group (data not shown).…”
Section: Cardiac Transcriptomementioning
confidence: 64%
“…Consumption of a diet high in fiber increases gut microbiota populations that generate short-chain fatty acids (SCFAs) such as acetate. [9][10][11] Gut microbiota dysbiosis has been recently associated with high BP in animal and human hypertension. 12 In the present study, we aimed to investigate whether dietary fiber or acetate supplementation, through changes in the gut microbiota, prevents the development of hypertension and associated renal and cardiac fibrosis in the deoxycorticosterone acetate (DOCA)-salt model.…”
Section: Fibre Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibre is fermented by colonic commensal bacteria to short-chain fatty acids (SCFAs). SCFAs are anti-inflammatory 24 , promote gut homeostasis 30 and epithelial integrity 4,29 , and regulate the size and function of the colonic Treg pool [25][26][27] . A recent study reported that dietary fibre and the SCFA propionate protected against allergic airway disease (AAD) in mice 6 .…”
mentioning
confidence: 99%
“…In general, the activation of GPR41 (or FFAR3) and GPR43 (or FFAR2) releases peptide YY and glucagon-like peptide-1 (GLP-1), which affect host satiety and intestinal gluconeogenesis. Besides, SCFAs signalling through GPR109A exerts antiinflammatory and anti-tumorigenic responses (Macia et al 2015). Butyrate and propionate to a lesser extent, can also be involved in the epigenetic regulation of host gene expression by inhibiting histone deacetylase (HDAC) (Fellows et al 2018).…”
Section: Comparative Genomics Reveal Thatmentioning
confidence: 99%